2022
DOI: 10.24018/ejfood.2022.4.5.570
|View full text |Cite
|
Sign up to set email alerts
|

Oleosin Expression Patterns and Size of Oil Bodies as a Factor in Determining Oil Content in Safflower (Carthamus Tinctorius L.) Genotypes

Abstract: The climate crisis and the Ukraine war have shown the vulnerability of various crop commodities. One of those badly affected is cooking oil, leading to a shortage in several countries. This coupled with the need for healthier cooking oil, increases proportionally with the world population and has resulted in escalated cooking oil prices. Thus, continued evaluation of alternative oil crops that can do well in marginal lands becomes a vital practice to undertake. Safflower is one of the marginalized oil crops wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
0
0
Order By: Relevance
“…Furthermore, the fact that genotype Gila was able to produce high oil content irrespective of the location and season showed that this genotype is very adaptable as compared to other genotypes concerning this trait. Mosupiemang et al (2022) found that the genotype Gila had the highest oleosin gene expression and a smaller oil body diameter which are characteristics of a high oil-producing genotype. Oil yield followed a similar trend with oil content and seed yield/ha because oil yield is a product of oil content and seed yield/ha.…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, the fact that genotype Gila was able to produce high oil content irrespective of the location and season showed that this genotype is very adaptable as compared to other genotypes concerning this trait. Mosupiemang et al (2022) found that the genotype Gila had the highest oleosin gene expression and a smaller oil body diameter which are characteristics of a high oil-producing genotype. Oil yield followed a similar trend with oil content and seed yield/ha because oil yield is a product of oil content and seed yield/ha.…”
Section: Discussionmentioning
confidence: 94%